Theoretical analysis of dynamic teams: Evolution and perspectives - Fernández-Gascueña, Elena; Reyes, Luisa-Eugenia; Pinillos, María-José (Revista de Ciencias Sociales, 2024)
This study aims to describe and analyze scientific production in relation to dynamic teams. Through bibliometric analysis, this article explores the most studied topics, the relationships between authors and their citations. The results show that the interest of researchers, according to the number of citations, is directed towards the fields of Psychology, Business and Organizational Behavior. Likewise, a certain dispersion is observed in the topics studied and there is a lack of consensus on the concept of a dynamic team. In conclusion, the present study provides an overview of how the literature in this scientific field has developed. Future research can be directed to the study of dynamic teams in different contexts, which could deepen the analysis for a definition of the concept of dynamic team and benefit from the multidisciplinary nature of the field, as well as facilitate the transfer of ideas between different fields.